Trabalho docente, família e vida pessoal : permanências, deslocamentos e mudanças contemporâneas - Santos, Silmere Alves (2012)
Having the historical-critical and feminist epistemology (considering the context of the Brazilian northeastern society and the processes of productive restructuring of the university) this research aimed at knowing the displacements, changes and permanence in the spheres of work, family and personal life, which make it difficult and/or possible to have more egalitarian and equitable relations amongst genders and/or point to other patterns of sociabilit favor the articulation between private/public spheres and amongst teachers who work in the Brazilian public university of the state of Sergipe. As to the methodology, the qualitative research showed its relevance by means of the case study. Its empirical field was the Federal University of Sergipe/São Cristóvão Campus and its academic centers: CCSA, CCBS, CCET, CECH. To collect data, various sources were used to trace teachers‟ profile such as websites (CNPQ, Ministry of Science and Technology, SBPC, ANDIFES, Council of University Rectors, IBGE, PNAD) and the 2008 Statistical Yearbook of the Federal University of Sergipe. Many theoretical categories were investigated like labor sexual division, vertical and horizontal segregation, glass ceiling, degeneration of work, amongst others. The concentration of male and female occupational groups was identified in a population of 323 (60,6%) men and 210 (39,4%) women, adding up 533 (100%) teachers of the permanent personnel, in 2008. One hundred seven closed-ended questionnaires and fourteen open questionnaires were applied. The results inform that in the context of teaching work at the Federal University of Sergipe, the sexual division and the horizontal and vertical segregation still prevail, unveiling the parallel segregation which composes the tridimensional segregation. Therefore the ghetto remains in the Science area; it is stated that productivity and substitute work are primarily occupied by the female sex. The subjects‟ representations point to family responsibilities which, towards love and maternal duties, women are the ones to assume, and they do not identify themselves as feminists, they are winners and losers of reflection; gender stereotypes appear as an expression of prejudice. As to personal life, data point to the fact that women rest less than eight hours a day, assume quadruple working hours, and amongst married women such hours are associated with their taking care of their children and of themselves. It can be said that the traditional archetypes linked to patriarchy, to the roles directed to women (cooking, sewing and taking care of someone) were substituted by studying, working, loving, giving birth to a child or not, and taking care of him/her, the latter not necessarily related to marriage or heterosexuality. Men‟s roles as the boss of the family and its provider were also displaced due to women‟s participation in the labor market, the increase in their level of schooling, the deterioration of economy for one to support one‟s family or due to the intensification of consumerism and reflective maternity. So, articulating work, family and personal life is not only an issue for women. It is an issue for both men and women as procreators of human beings; for the State as it is a social matter, and therefore, must be the object of public policies; for the organizations as the object of actions which require social responsibility and for the society, organized from a perspective of collective performance aiming at fighting for egalitarian and equitable human rights.